Comparative investigation of hollow mesoporous NiCo2S4 ellipsoids with enhanced pseudo-capacitances towards high-performance asymmetric supercapacitors. (1st October 2016) - Hou, Linrui; Bao, Ruiqi; Chen, Zhiyi; Rehan, Muhammad; Tong, Liuniu; Pang, Gang; Yuan, Changzhou
Graphical abstract: Hierarchical hollow mesoporous NiCo2 S4 ellipsoids were smartly fabricated, and exhibited large specific capacitances/energy density, and excellent cycling stability at high rates for advanced next-generation asymmetric supercapacitors. Highlights: Hollow mesoporous NiCo2 S4 ellipsoids were scalablly fabricated. Hollow NiCo2 S4 ellipsoids showed better supercapacitances than NiCo2 O4 . Hollow NiCo2 S4 -based hybrid cell exhibited high specific energy density. Hollow NiCo2 S4 -based asymmetric device owned superior cycling stability. Underlying reasons for enhanced capacitances were comparatively unconvered. Abstract: In the contribution, we explore an efficient synthetic platform to purposefully fabricate hollow mesoporous NiCo2 S4 (HM-NCS) ellipsoids for advanced electrochemical supercapcitors (ECSs). Uniform hollow NiCo2 O4 (NCO) as the intermidate is initially prepared by calcination, and subsequently chemically transformed into spinel HM-NCS ellipsoids through in situ anion-exchange reaction. Elaborate physicochemical and electrochemical investigations comparatively demonstrate that the resultant HM-NCS ellipsoids possess superior pseudo-capacitance of ∼495 F g −1 against its hollow NCO counterpart (∼185 F g −1 ) at the same rate of 10 A g −1, benefiting from its larger surface area, thinner porous shells, smaller internal and charge-transfer resistances, and higher-content Ni (II)/Co (II) species. Remarkably, an asymmetric supercapacitor assembled with HM-NCS ellipsoids obtains a high energy density of ∼28.9 Wh kg −1 at a power density of ∼187.5 Wh kg −1, and appealing cycle behaviors with a capacitance decay of ∼0.0058% per cycle over 5000 cycles at a high rate of 3 A g −1 . It strongly highlights that the cost-effective HM-NCS ellipsoids would be a competitive pseudo-capacitive electrode candidate for advanced ECSs applications.